Developing Instagram Reels-Based Instructional Media for Teaching Simple Present Tense in Higher Education - Nur Mardiyani Fauziah Fuad; Nursalim; Fitri Arniati (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
This study investigates the development of Instagram Reels-based learning media for teaching the simple present tense to non-English major students in higher education. Although social media integration in English Language Teaching (ELT) has increased significantly, limited studies have examined the pedagogical potential of short-form video microlearning for grammar instruction among non-English major students in Indonesian higher education contexts. This study addresses this gap by integrating Instagram Reels, microlearning principles, and digital pedagogy into grammar learning. The research employed a Research and Development (R&D) design using the 4D model consisting of Define, Design, Develop, and Disseminate stages. The participants were students from the Physical Education and Civic Education study programs at Universitas Pendidikan Muhammadiyah Sorong. Data were collected through observations, interviews, questionnaires, expert validation, and pre-test and post-test assessments. The findings revealed that the Instagram Reels-based learning media improved students’ grammar achievement, with Physical Education students increasing from 50% to 80% and Civic Education students from 55% to 83%. The media also enhanced students’ motivation, participation, and learning engagement through concise, contextual, and visually interactive grammar instruction. This study contributes theoretically to digital ELT pedagogy by demonstrating the effectiveness of social media-based microlearning in supporting grammar learning among non-English major students in higher education.